PREPARATION OF PLASTICINE HANDLE DETAIL BY STAMPING METHOD (Conferencea, 2024)
This research is aimed at studying the process of preparing plasticine handle details through the stamping method. Stamping is an effective and economical technology used for metal forming and cutting, and is widely used in the automotive industry.